Should differences be included? : On a wrongly framed problem and an unbearable reality - Skliar, Carlos (2008)
This paper proposes an ethical reinterpretation of the right to education of persons with disabilities, with emphasis being made on the situation in Latin America . After consideration of juridical systems, political funding methods, inclusion percentages and follow-up programmes for disabled people of schooling age, a series of issues on the idea of educational training, of being with others and about the ethical responsibilities in the task of teaching.